The ​ Effect of the Pandemic on Micro, Small, and Medium Enterprises in CALABARZON. - Winona Miranda Reb Suministrado; Jona Marie Fernandez; Alessandra Mae Ramos; Marie Antoinette Rosete (UJoST- Universal Journal of Science and Technology, 2023)
This study aims to view the effects of the Coronavirus Disease 2019 (COVID-19) pandemic on Micro, Small, and Medium Enterprises (MSMEs), focusing on the area of CALABARZON, wherein it is the epicenter of the pandemic. This study aims to understand the impact of COVID-19 in terms of MSMEs' performance, measured by their ability to generate employment and sales, along with how their operation responds to the effects of the pandemic. The study would like to state if there is a connection between the restrictions and limited activities of the COVID-19 pandemic to the state and condition of businesses in CALABARZON, particularly those belonging to the micro, small and medium-scale one. This study also shows the bigger picture of the COVID-19 pandemic affecting the business sector in the provinces. Keywords: COVID-19, MSMEs, Sales, Employment, Innovation